A Brief Observational History of the Black-Hole Spacetimes - Wolfgang Kundt (Advances in Mathematical Physics)
In this year (2015), black holes (BHs) celebrate their 100th birthday, if their birth is taken to be triggered by a handwritten letter from Martin Schwarzschild to Albert Einstein, in connection with his newly found spherically symmetric vacuum solution.